2016
DOI: 10.2147/ijn.s99692
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid reagent functional chitosan-PEI conjugate with AQP2-siRNA suppressed endometriotic lesion formation

Abstract: To identify a new drug candidate for treating endometriosis which has fewer side effects, a new polymeric nanoparticle gene delivery system consisting of polyethylenimine-grafted chitosan oligosaccharide (CSO-PEI) with hyaluronic acid (HA) and small interfering RNA (siRNA) was designed. There was no obvious difference in sizes observed between (CSO-PEI/siRNA)HA and CSO-PEI/siRNA, but the fluorescence accumulation in the endometriotic lesion was more significant for (CSO-PEI/siRNA)HA compared with CSO-PEI/siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
(37 reference statements)
1
32
0
Order By: Relevance
“…Furthermore, observations under an electron microscope showed no obvious toxic effects on reproductive organs and confirmed that the (CSO-PEI/ siRNA)HA gene delivery system can be used as a safe and effective way for the treatment of endometriosis. 16 Additional research related to molybdenum NPs includes phosphate glasses incorporating vanadium and molybdenum oxides as useful compounds for the control of drug dissolution and drug release. The modified vancomycin molecules demonstrate greater hydrogen bonding with vanadium-doped glasses and consequently slower drug release over 14 days showing an improved surface modification with drug molecules.…”
Section: Polymer Nanocomposite (Pnc)mentioning
confidence: 99%
“…Furthermore, observations under an electron microscope showed no obvious toxic effects on reproductive organs and confirmed that the (CSO-PEI/ siRNA)HA gene delivery system can be used as a safe and effective way for the treatment of endometriosis. 16 Additional research related to molybdenum NPs includes phosphate glasses incorporating vanadium and molybdenum oxides as useful compounds for the control of drug dissolution and drug release. The modified vancomycin molecules demonstrate greater hydrogen bonding with vanadium-doped glasses and consequently slower drug release over 14 days showing an improved surface modification with drug molecules.…”
Section: Polymer Nanocomposite (Pnc)mentioning
confidence: 99%
“…Clearly, significantly higher accumulation of both NIR dye-labeled HA was observed in the liver, which is responsible for the elimination of HA from the circulation. 59,60 Besides, it was found that HA-NIR accumulated in the tumor region, indicating active targeting ability of HA in CD44 receptor overexpressing tumors. 61,62 HA-NIR was also found to be present in spleen and heart.…”
mentioning
confidence: 99%
“…In the emerging field of nanotechnology, nanoparticle platforms have also demonstrated great potential for detection, diagnosis, and treatment of human infertility. Most reports have explored the use of nanomaterials for the detection and therapy of reproductive cancers and noncancer conditions, such as uterine leiomyoma (Shalaby et al, ) and endometriosis (Liu et al, ; Zhao et al, ). However, a growing number of studies have applied nanotechnology in reproductive biology to target and sort specific populations of gametes and to optimize gene transfer and editing methodologies (Barkalina, Charalambous, Jones, & Coward, ; Remião et al, ).…”
Section: Nanotechnologymentioning
confidence: 99%
“…In the emerging field of nanotechnology, nanoparticle platforms have also demonstrated great potential for detection, diagnosis, and treatment of human infertility. Most reports have explored the use of nanomaterials for the detection and therapy of reproductive cancers and noncancer conditions, such as uterine leiomyoma (Shalaby et al, 2016) and endometriosis Zhao et al, 2016).…”
Section: Nanotechnologymentioning
confidence: 99%